Reprogramming of Mitochondrial Respiratory Chain Complex by Targeting SIRT3‐COX4I2 Axis Attenuates Osteoarthritis Progression. Issue 10 (22nd January 2023) - Zhang, Yijian; Liu, Yang; Hou, Mingzhuang; Xia, Xiaowei; Liu, Junlin; Xu, Yong; Shi, Qin; Zhang, Zhongmin; Wang, Liang; Shen, Yifan; Yang, Huilin; He, Fan; et al.
Abstract: Mitochondrial homeostasis is of great importance for cartilage integrity and associated with the progression of osteoarthritis (OA); however, the underlying mechanisms are unknown. This study aims to investigate the role of mitochondrial deacetylation reaction and investigate the mechanistic relationship OA development. Silent mating type information regulation 2 homolog 3 (SIRT3) expression has a negative correlation with the severity of OA in both human arthritic cartilage and mice inflammatory chondrocytes. Global SIRT3 deletion accelerates pathological phenotype in post‐traumatic OA mice, as evidenced by cartilage extracellular matrix collapse, osteophyte formation, and synovial macrophage M1 polarization. Mechanistically, SIRT3 prevents OA progression by targeting and deacetylating cytochrome c oxidase subunit 4 isoform 2 (COX4I2) to maintain mitochondrial homeostasis at the post‐translational level. The activation of SIRT3 by honokiol restores cartilage metabolic equilibrium and protects mice from the development of post‐traumatic OA. Collectively, the loss of mitochondrial SIRT3 is essential for the development of OA, whereas SIRT3‐mediated proteins deacetylation of COX4I2 rescues OA‐impaired mitochondrial respiratory chain functions to improve the OA phenotype. Herein, the induction of SIRT3 provides a novel therapeutic candidate for OA treatment. Abstract : The SIRT3‐medicated post‐translational acetylation of the mitochondrial respiratory chain has therapeutic potential for the treatment of osteoarthritis (OA). Mechanistically, SIRT3 directly binds and deacetylates COX4I2 to promote mitochondrial respiration activity. Meanwhile, SIRT3‐mediated deacetylation of SOD2 reinforces mitochondrial intrinsic antioxidant properties. Synergistically, strengthening mitochondria by SIRT3 ensures extracellular matrix anabolism and catabolism dynamic balance to ultimately achieve OA amelioration.